1995
DOI: 10.1136/bmj.310.6978.489
|View full text |Cite
|
Sign up to set email alerts
|

Relation between maternal haemoglobin concentration and birth weight in different ethnic groups

Abstract: Objective-To assess the relation of the lowest haemoglobin concentration in pregnancy with birth weight and the rates oflow birth weight and preterm delivery in different ethnic groups.Design Conclusions-The magnitude ofthe fall in haemoglobin concentration in pregnancy is related to birth weight; failure of the haemoglobin concentration to fall below 105 g/l indicates an increased risk of low birth weight and preterm delivery. This phenomenon is seen in all ethnic groups. Some ethnic groups have higher rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
199
5
19

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(236 citation statements)
references
References 19 publications
13
199
5
19
Order By: Relevance
“…28 Physiological plasma volume expansion might be necessary and even beneficial during pregnancy, 33 but, as we found, severe anemia might have adverse effects as found by others. [34][35][36][37] We found an association between severe anemia and LBW when assessing Hb in the third trimester of pregnancy. Villar and Belizan 38 found that negative factors for fetus' growth around the 30th week of gestation resulted in a disproportionately growth-retarded infant.…”
Section: Discussionmentioning
confidence: 91%
“…28 Physiological plasma volume expansion might be necessary and even beneficial during pregnancy, 33 but, as we found, severe anemia might have adverse effects as found by others. [34][35][36][37] We found an association between severe anemia and LBW when assessing Hb in the third trimester of pregnancy. Villar and Belizan 38 found that negative factors for fetus' growth around the 30th week of gestation resulted in a disproportionately growth-retarded infant.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, Turkey et al (1995) reported that they were not able to detect any correlation between maternal ferritin, haemoglobin and newborn gestational age, haemoglobin and birthweight. Steer et al (1995) in a retrospective analysis of 153 602 pregnancies found that the maximum mean birthweight in white women was achieved with a lower haemoglobin concentration in pregnancy of 8.5±9.5 gadl and concluded that the failure of the haemoglobin concentration to fall below 10.5 gadl indicates an increased risk of low birthweight and preterm delivery and that this phenomenon was seen in all ethnic groups in his study.…”
Section: Discussionmentioning
confidence: 99%
“…result >3 standard deviations (SD) higher than the mean of the reference population (i.e., a Hb concentration of >15.0 g/dL or a Hct of >45.0%), particularly in the second trimester, likely indicates poor blood volume expansion (72 ). High Hb concentration or Hct has been associated with hypertension and poor pregnancy outcomes (e.g., fetal growth retardation, fetal death, preterm delivery, and low birthweight) (75)(76)(77)(78). In one study, women who had a Hct of ≥43% at 26-30 weeks' gestation had more than a twofold increased risk for preterm delivery and a fourfold increased risk for delivering a child having fetal growth retardation than did women who had a Hct of 33%-36% (76 ).…”
Section: Hb Concentration and Hematocritmentioning
confidence: 99%